Optimising soil physical properties for rehabilitation of mined land – effects of tine type on soil strength and root proliferation - Lardner, TD; Worthington, TR; Braimbridge, MF; Vlahos, S; Tibbett, M (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
Deep ripping of mine floors after bauxite mining is standard practice carried out prior to overburden and topsoil return to alleviate the soil compaction caused by trafficking of heavy machinery. A field trial was conducted to compare the effects of deep ripping practices using straight and winged tines, with an unripped control, on the physical properties of regolith within three rehabilitated bauxite mine pits. The subsequent effect on root development was also assessed two years after deep ripping. Ripping reduced soil strength and increased root abundance and depth of root penetration, irrespective of the type of pit floor materials present. However, there was a contrast in tine performance depending on the materials being ripped. The winged tine produced significantly lower penetration resistance in more friable, sandy soils, while the straight tine outperformed the winged tine in heavier, more clayey soils. Despite the differences in soil strength reduction between tine types in these different materials, there was no corresponding difference in root proliferation. Provided that soil strength was reduced to a critical threshold (about 35 N or less) over a sufficient area, roots proliferate to a similar extent, regardless of whether there are zones of lower strength present. The benefits conferred by deep ripping appeared to be highly dependent on the physical properties of the soil materials present so the effects of deep ripping will not necessarily be consistent across all rehabilitation areas.